Maya market women : power and tradition in San Juan Chamelco, Guatemala - Kistler, S. Ashley, 1978- (Interpretations of culture in the new millennium., 2014)
"As cultural mediators, Chamelco's market women offer a model of contemporary Q'eqchi' identity grounded in the strength of the Maya historical legacy. Guatemala's Maya communities have faced nearly five hundred years of constant challenges to their culture, from colonial oppression to the instability of violent military dictatorships and the advent of new global technologies. In spite of this history, the people of San Juan Chamelco, Guatemala, have effectively resisted significant changes to their cultural identities. Chamelco residents embrace new technologies, ideas, and resources to strengthen their Indigenous identities and maintain Maya practice in the 21st century, a resilience that sets Chamelco apart from other Maya towns. Unlike the region's other Indigenous women, Chamelco's Q'eqchi' market women achieve both prominence and visibility as vendors, dominating social domains from religion to local politics. These women honor their families' legacies through continuation of the inherited, high-status marketing trade. In Maya Market Women, S. Ashley Kistler describes how market women gain social standing as mediators of sometimes conflicting realities, harnessing the forces of global capitalism to revitalize Chamelco's Indigenous identity. Working at the intersections of globalization, kinship, gender, and memory, Kistler presents a firsthand look at Maya markets as a domain in which the values of capitalism and Indigenous communities meet"--